Efektivitas Metode Demonstrasi Berbasis Tugas Dalam Meningkatkan Kemampuan Mengurut Bilangan Bagi Anak Tunagrahita Kelas V Di SDLB Negeri 087706 Sibolga - Siregar, Titiennur; Ardisal, Ardisal (Jurnal Penelitian Pendidikan Khusus, 2022)
This article is motivated by researchers who found difficulty in sorting numbers in students with mild mental disabilities from SDLB Negeri 087706 Sibolga. The purpose of this learning is to improve your ability to sort numbers using a task-based demonstration method. This study uses a single subject research (SSR) approach with an A-B-A design and graphical visual analysis techniques. This type of variable measurement is frequency dependent. The data collection technique used is his 20-item test per session. Overall, the results of this study demonstrate that using a task-based demonstration method significantly improves the number sorting skills of students with intellectual disabilities. This improvement in ability is demonstrated by first measuring the student's ability (A1). The frequency of detection was 2, 4, 4, 4. Moreover, after the researcher performed intervention (B), he found frequencies higher than 10, 13, 15, 18, 20, 20 in his seven sessions of the task-based demonstration method. 20. Subject also reached maximum frequency when the intervention ended with her 20, 20 points. The results of this study show that using a task-based demonstration method improves number sorting ability.